Challenge: Modelling Unit Commitment as a Planning Problem - Campion, Joshua; Dent, Chris; Fox, Maria; Long, Derek; Magazzeni, Daniele (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
Unit Commitment is a fundamental problem in power systems engineering, deciding which generating units to switch on, and when to switch them on, in order to efficiently meet anticipated demand. It has traditionally been solved as a Mixed Integer Programming (MIP) problem but upcoming changes to the power system drastically increase the MIP solution time. In this paper, we discuss the benefits that using planning may have over the established methods.We provide a formal description of Unit Commitment, and we present its formulation as MIP and as a planning problem. This is a novel and interesting application area for planning, with features that make the domain challenging for current planners.